El médico como profesor universitario: percepción de un grupo de académicos del Departamento de Medicina del Hospital Clínico de la Universidad de Chile - Cortés S., Esteban (Revista Hospital Clínico Universidad de Chile, 2009)
A mixed, quantitative and qualitative methodology was performed to analyze the reflections raised in a group of academic physicians from the Department of Medicine of the University of Chile Clinical Hospital, concerning their knowledge about teaching and learning techniques used in the area of health sciences. The investigation was focused in the analysis of the instruments employed to obtain information data allowing interpretation of intentions and actions that induced and maintained in students the pertinent knowledge and skills development. Thus having become and perform as full graduate health professionals, by demonstrating to have achieved the proper competences that characterizes each working role and assure effectiveness and satisfaction of patients with respect to their accomplishments. Twenty academics from the before mentioned unit were submitted to a semi structured interview and a self administered questionnaire, to evaluate their teaching performance before and after reviewing new knowledge acquired and the learning techniques incorporated. Subsequently, the results obtained were analyzed by focus groups of five academics. Triangulation of results among the two groups showed that academics do not perform a systematic reflection regarding their teaching practices, which is lacking of professional skills most needed by the teachers engaged in a work environment that requires them, prioritizing are.